2014
DOI: 10.1136/annrheumdis-2014-206237
|View full text |Cite
|
Sign up to set email alerts
|

The antibody response against human and chimeric anti-TNF therapeutic antibodies primarily targets the TNF binding region

Abstract: BackgroundIn a subset of patients, anti tumour necrosis factor (TNF) therapeutic antibodies are immunogenic, resulting in the formation of antidrug antibodies (ADAs). Neutralising ADAs compete with TNF for its binding site and reduces the effective serum concentration, causing clinical non-response. It is however unknown to which extent ADAs are neutralising.ObjectivesTo study which proportion of antibodies to human(ised) anti-TNF (adalimumab, golimumab, certolizumab) as well as chimeric anti-TNF (infliximab) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 11 publications
4
77
0
2
Order By: Relevance
“…In the case of adalimumab, a fully human anti-TNF agent, recent data indicate that essentially all ADA are anti-idiotypic antibodies, directed against the TNF binding region of adalimumab and resulting in neutralization of the drug (8). This is confirmed by inhibition experiments showing that TNF completely prevents binding of ADA in patient sera (9). These observations suggest that the immune response against adalimumab is restricted, but it leaves unanswered the question of whether the immune system targets just a single epitope or multiple determinants that are spatially confined to the TNF-binding site on adalimumab.…”
supporting
confidence: 57%
“…In the case of adalimumab, a fully human anti-TNF agent, recent data indicate that essentially all ADA are anti-idiotypic antibodies, directed against the TNF binding region of adalimumab and resulting in neutralization of the drug (8). This is confirmed by inhibition experiments showing that TNF completely prevents binding of ADA in patient sera (9). These observations suggest that the immune response against adalimumab is restricted, but it leaves unanswered the question of whether the immune system targets just a single epitope or multiple determinants that are spatially confined to the TNF-binding site on adalimumab.…”
supporting
confidence: 57%
“…[25][26][27] Notably, for both monoclonal and polyclonal anti-adalimumab antibodies, no cross-reactivity was observed to infliximab. 26,27 A study on the actual binding sites of anti-adalimumab antibodies revealed that the antibody response against adalimumab is highly restricted.…”
Section: Anti-idiotype Antibodiesmentioning
confidence: 99%
“…Strikingly, >90% of the antibody response to the chimeric infliximab could be inhibited by TNF. 25 Several cases were identified with a small but definite fraction of non-neutralizing antibodies (i.e., <10%) that were not cross-reactive to polyclonal mouse IgG, suggesting that infliximab-specific idiotopes outside of the antigen binding site were recognized.…”
Section: Anti-idiotype Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaten bu nedenle, araflt›rma amaçl› d›-fl›nda, anti-TNF alan hastalarda rutin anti-ilaç antikorlar›n›n bak›lmas› önerilmemektedir. [4,21,[33][34][35] • Otoimmün yan etkiler: Yaklafl›k %40 olguda antinükleer antikor pozitifli¤i geliflir ve süre uzad›kça bu s›kl›k artar. Temel mekanizma normalde TNF'nin inhibe etti¤i IL-10 ve IFN-α düzeylerindeki art›flt›r.…”
Section: Raedunclassified